2020
DOI: 10.1177/0192513x19895043
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Child Experiences of Parental Work–Family Conflict and Satisfaction with Work and Family

Abstract: This study examined the relationship between parent and young adult child perceptions of parental work–family conflict and work and family satisfaction. Data were collected from 112 parent–child dyads, and children perceived parents to experience significantly more strain-based work–family conflict than parents reported. Parent and child did not differ in ratings of five other dimensions of parent’s work–family and family–work conflict. Parent and child ratings of the parent’s experience of all three dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
(59 reference statements)
2
5
0
Order By: Relevance
“…Moreover, according to the matching hypothesis, the primary effects of a conflict are found in the domain in which the conflict originates (Amstad et al, 2011). As evidence supports both hypotheses at intra-individual and inter-individual levels (Amstad et al, 2011; Li et al, 2021 ; Matei et al, 2021 ; Morr & Droser, 2020 ; Drummond et al, 2017 ), we pose that family-to-work conflict indirectly reduces family satisfaction via a reduction of job satisfaction. In other words, if individuals cannot meet the demands at work due to family interference with their job they will experience job dissatisfaction, which in turn may generate a negative affective reaction against family, thus negatively influencing family satisfaction.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Moreover, according to the matching hypothesis, the primary effects of a conflict are found in the domain in which the conflict originates (Amstad et al, 2011). As evidence supports both hypotheses at intra-individual and inter-individual levels (Amstad et al, 2011; Li et al, 2021 ; Matei et al, 2021 ; Morr & Droser, 2020 ; Drummond et al, 2017 ), we pose that family-to-work conflict indirectly reduces family satisfaction via a reduction of job satisfaction. In other words, if individuals cannot meet the demands at work due to family interference with their job they will experience job dissatisfaction, which in turn may generate a negative affective reaction against family, thus negatively influencing family satisfaction.…”
Section: Introductionsupporting
confidence: 72%
“…Drummond et al, ( 2017 ) found that work-to-family conflict and family-to-work conflict negatively correlated with both job and family satisfaction, although when they tested the relationship between family-to-work conflict and family and job satisfaction one year later, the relationship between family-to-work conflict and family satisfaction was stronger than the relationship between family-to-work conflict and job satisfaction, also providing more support to the matching theory. In addition, Morr and Droser ( 2020 ) also provides provide support to the matching theory, as they found that a behavior- and strain-based family interference with work correlated negatively with family satisfaction. Therefore, we expect a negative relationship between family-to-work conflict and family satisfaction based on the matching hypothesis, and a negative relationship between family-to-work conflict and job satisfaction based on the cross-domain hypothesis.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The APIM is the most frequently used analytical model of dyadic data (Garcia et al, 2015 ) because it simultaneously estimates the effects of an individual’s attributes on their own outcome variable (actor effect), as well as their partner’s (partner effect). The APIM has been used to investigate complex dynamics in family members and other close relationships, such as the association between parents’ work-family conflict and enrichment and their children’s problem behaviours (Vieira et al, 2016 ), the relationship between couples’ depression and relationship satisfaction (Li & Johnson, 2018 ), the link between parent and child experiences of parental work-family conflict (Morr & Droser, 2020 ), the association between fathers’ parenting uplifts and mothers’ life satisfaction (Chen, 2020 ), and the relationship between parents’ work-family conflict and enrichment and their adolescent children’s well-being (Matias & Recharte, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, WLB does not imply only the reduction in parental stress by creating and maintaining a symmetrical balance between different spheres of life (Ford and Collinson, 2011), but also the time for personal pleasures that lead to family wellbeing (Bradley et al, 2008). Looking at WLB from a child's perspective, Morr Loftus and Droser (2020) found that children believe parents are less satisfied with both family and work than they show at home. Since parents model their children's attitudes towards future work and family, it is important to consider children's expectations of their parents' workplace versus HR strategies aimed at achieving wellbeing for working parents.…”
Section: Introductionmentioning
confidence: 99%